The Influence of Financial Ratio on Stock Return of Mining Companies Listed on IDX For The 2018-2021 Period - Pratama, Oscar Jovi; Hasibuan, Thezar Fiqih Hidayat (Accounting and Business Journal, 2023)
The aim of this research is to determine the influence of Current Ratio (CR), Debt to Asset Ratio (DAR), and Earning per Share (EPS) on stock returns of coal sub-sector mining companies listed on the Indonesia Stock Exchange in 2018-2021. This type of research is a causal effect with a quantitative approach. The sample for this research is 84 sample data consisting of 21 financial reports for 4 years of research. The type of data in this research is secondary data. The analytical method in this research uses multiple regression analysis with CR research results partially having a positive and significant effect on stock returns, DAR partially having a negative and significant effect on stock returns, and EPS having no effect on stock returns and the results of the F test having a positive and significant effect .